Writing A Video Script to Promote Balaputra Dewa Museum as A Cultural Tourism Attraction in Palembang - Achmad Leofaragusta K K; Wasitoh Meirani; M Bambang Purwanto (BADAN PENERBIT STIEPARI PRESS, 2025)
This study explores the role of the Balaputra Dewa Museum in preserving and promoting the cultural heritage of Palembang. As one of the most significant historical sites in South Sumatra, the museum serves as a key attraction for cultural tourism. This research highlights how the museum contributes to cultural preservation and tourism development by analyzing its exhibits, educational programs, and visitor engagement strategies. Findings indicate that interactive learning experiences and traditional architecture, such as the Rumah Limas, are crucial in enhancing visitor engagement. This study emphasizes the importance of integrating historical education with tourism to strengthen cultural appreciation and economic sustainability in the region.